Menakar Kesuksesan Penerapan Kurikulum Berbasis Cinta dalam Melahirkan Generasi Berkarakter Toleran dan Inklusif - Keo, Marianus (Sekolah Tinggi Agama Katolik Negeri Pontianak, 2025)
The background of this study is the increasing of exclusivism in religious education, which has led to a decline in students’ tolerant and inclusive attitudes. The purpose of this research is to assess the effectiveness of the Love-Based Curriculum in shaping a tolerant and inclusive generation. This research employed a library-based method by reviewing books, journals, and relevant scientific reports that discussed the relationship between love, education, and character formation. The data were analyzed using content analysis techniques to identify patterns of meaning and the relevance of love values in education. The findings indicated that the Love-Based Curriculum plays a strategic role in fostering interfaith human awareness and provides a conceptual contribution to the development of a humanistic model of religious education grounded in the values of love. The conclusion of this study is that love can transform into a pedagogical foundation in religious education to build tolerant and inclusive character. The research shows that when love is made a curriculum principle, it works not only as a moral value but also as a pedagogical mechanism capable of transcending religious and ideological barriers.